EPIC OF DERWÊŞÊ EVDÎ AND EDÛLÊ FORM THE PERSPECTIVE OF ETHNIC AND RELLIGOUS ATTITUDES - Atlı, Hikmettin (Humanities Journal of University of Zakho, 2022)
National epics are very important in the expression of social identities that we gain insights into society through research on them. This type of knowledge, although not based on historical documents, is in some way show us the emotional tendencies, hopes, perceptions of the past and future of that social group. As religious, social classes, gender, and ethnic groups emerge within society, so we see that folklore narratives reflect this diversity of society. Each folk epic, contains many social characteristics both from its own time and before its own time and transmits them to the future. Therefore the study of folk epics is also a study of society. Through reading and analytical research on these texts we also gain a lot of information about the reflexes of that society. In this study, we will look at some variants of the Epic of Derwêşê Evdî and Edulê and try to show how these types of folklore texts become the subject of societal claims of identity. These variants that we will examine in our study were compiled from the Kurdish Muslim community and the Yezidi Kurds.